Antibacterial and anti-inflammatory ZIF-8@Rutin nanocomposite as an efficient agent for accelerating infected wound healing - Xia, Xiaomin; Song, Xujun; Li, Ying; Hou, Wenxue; Lv, Hanlin; Li, Feng; Li, Yanan; Liu, Jie; Li, Xue (Frontiers in Bioengineering and Biotechnology, 2022)
Essentially, wound healing is a complicated physiological process in which there exists an interaction between the organism's immune regulation and antimicrobial therapy. However, multiple drug-resistant bacteria implicated in chronic non-healing wound are not merely impeding the cure process, but more than a burden on economic and social development. Due to the inefficiency of conventional antibiotics, nanomedicine in the biomedical field is emerging as a prospective anti-infective therapy method. Herein, a novel nano-drug with antibacterial and anti-inflammatory characteristics was synthesized by loading Rutin into zeolitic imidazolate framework-8 (ZIF-8), abided by the principle of electrostatic adsorption. The synthetic ZIF-8 loaded Rutin (ZIF-8@Rutin) was affirmed by testing the changes in the diameter and chemical functional group. Interestingly, the ladened Rutin afforded nanocomposite with anti-inflammatory activity by its antioxidant capacity for the polarization of macrophages. Further, the prepared ZIF-8@Rutin exhibited highly effective antibacterial activity against Escherichia coli and Staphylococcus aureus in vitro. More importantly, it could shorten the infected wound healing process and alleviate the inflammation around the wound in vivo. Also, ZIF-8@Rutin had acceptable cytocompatibility. Thus, ZIF-8@Rutin may become a multifunctional nanomedicine with anti-inflammatory and bactericidal properties to promote infected wound healing.